Implementasi Arsitektur Semiotik pada Galeri Street Art di Kota Bandung - Qonitah Hanan Subagyo; Kusumaningdyah Nurul Handayani; Maya Andria Nirawati (Universitas Sebelas Maret Surakarta, 2023)
Semiotic architecture is a bridge between architects and users who convey architectural information. The application of semiotic architecture to street art gallery buildings can be used as street art introduction images to users. Unfortunately, there is no research on the relationship between semiotic architecture and street art that can be used as design criteria parameters. Therefore, the urgency of this research is to find out which components of semiotic architecture are most suitable for the identity of street art galleries. The method of this research is studying the characteristics of street art and then analyzing it with three semiotic architectural theories from Yousafi, Uluğ and Huang & Zhou. This research produces the design criteria of a street art gallery, namely the use of polychromatic colors, the use of dominant walls, designing space without partitions, materials that give the impression of a street, and incorporating public street art interaction content.